Assessment of anisotropic mechanical properties of a 3D printed carbon whisker reinforced composite. (3rd September 2019) - Bakis, Charles E.; Haluza, Rudy T.; Bartolai, Joseph; Kim, Jeffrey J.; Simpson, Timothy W.
Abstract : A commercial carbon whisker reinforced polylactic acid composite made by a type of three-dimensional (3D) printing known as material extrusion additive manufacturing is investigated. The primary objective is to experimentally characterize and model the direction-dependent tensile modulus of elasticity of unidirectionally printed composite material to assess the degree of anisotropy induced during printing and to determine how well the measured properties can be predicted by multiscale mechanics-based models. The model predictions are based on microstructural characteristics such as the aspect ratio and orientation of the whiskers and the constituent volume fractions. Other material characteristics are assumed, such the cylindrical shape of voids in the matrix and the perfect bonding condition of the whiskers. The experiments indicate (1) that the modulus in the 0-deg. printed direction can be at least twice the modulus in the 90-deg. printed direction and (2) that whisker alignment is improved during printing. Two models accounting for imperfect whisker alignment are used to predict the modulus of the 0-deg. material reasonably well, although the 90-deg. modulus is over-predicted by both models. The 0-deg. direction is roughly two times stronger than the 90-deg. direction in tension.